LRRK2 phosphorylates pre-synaptic N-ethylmaleimide sensitive fusion (NSF) protein enhancing its ATPase activity and SNARE complex disassembling rate - Belluzzi, Elisa (Mol Neurodegener, 2016)
BACKGROUND: Lrrk2, a gene linked to Parkinson’s disease, encodes a large scaffolding protein with kinase and GTPase activities implicated in vesicle and cytoskeletal-related processes. At the presynaptic site, LRRK2 associates with synaptic vesicles through interaction with a panel of presynaptic proteins. RESULTS: Here, we show that LRRK2 kinase activity influences the dynamics of synaptic vesicle fusion. We therefore investigated whether LRRK2 phosphorylates component(s) of the exo/endocytosis machinery. We have previously observed that LRRK2 interacts with NSF, a hexameric AAA+ ATPase that couples ATP hydrolysis to the disassembling of SNARE proteins allowing them to enter another fusion cycle during synaptic exocytosis. Here, we demonstrate that NSF is a substrate of LRRK2 kinase activity. LRRK2 phosphorylates full-length NSF at threonine 645 in the ATP binding pocket of D2 domain. Functionally, NSF phosphorylated by LRRK2 displays enhanced ATPase activity and increased rate of SNARE complex disassembling. Substitution of threonine 645 with alanine abrogates LRRK2-mediated increased ATPase activity. CONCLUSIONS: Given that the most common Parkinson’s disease LRRK2 G2019S mutation displays increased kinase activity, our results suggest that mutant LRRK2 may impair synaptic vesicle dynamics via aberrant phosphorylation of NSF. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13024-015-0066-z) contains supplementary material, which is available to authorized users.